An Unusual Case of an Acquired Aortopulmonary Fistula after Surgical Replacement of a Bicuspid Aortic Valve. (24th September 2021) - Khalid, Y.; Dasu, N.; Daneshvar, M.; Jang, P.; Patel, A.; Dasu, K.; Shah, A.
Abstract : Aortopulmonary fistulas are extremely rare and often occur as a result of long-standing aortic aneurysms. They are most frequently due to the erosion of a false aneurysm of the ascending or descending thoracic aorta into the pulmonary artery. Patients generally present with symptoms of acute decompensated heart failure due to a sudden formation of a left-to-right shunt. Here, we present the case of a 63-year-old male who acquired an aortopulmonary fistula four months after undergoing successful bioprosthetic aortic valve replacement.